Community-based management of freshwater resources: A practitioners’ guide to applying TNC’s Voice, Choice, and Action framework - Zhang, Wei; ElDidi, Hagar; Swallow, Kimberly A.; Meinzen-Dick, Ruth S.; Ringler, Claudia; Masuda, Yuta; Aldous, Allison (Nature Conservancy, 2020)
Despite being one of the most critical resources for all life on Earth, freshwater represents only 3 percent of the planet’s water supply, but only 0.5 percent is readily accessible to humans. In addition, the available freshwater resources (FWR) are unequally distributed across the globe, so many areas and populations face issues of water scarcity and quality. FWR are under enormous stress from agricultural systems, climate change, and other factors directly linked to human behavior—including population growth and industrialization. Moreover, the institutions intended to manage FWR under stress may be ill-equipped to do so, especially in the context of multiple, often competing claims on FWR and the complexity of water flows across time and space. Growing awareness of these challenges has given rise to a sense of urgency to raise attention and catalyze action toward improving the management of FWR, especially at the local level. This guide aims to advance the understanding of how communities can sustainably manage FWR by applying The Nature Conservancy’s Voice, Choice, and Action (VCA) framework. The original framework focused more on terrestrial resources but has been adapted here to address the unique characteristics of FWR. These characteristics present significant implications for sustainable resource management and, therefore, need to be taken into account in the design and implementation of community-based conservation (CBC) programs.